Extractable calcium, magnesium, potassium and sodium in diefferent peat types - Jaakko Kivekäs; Armi Kaila (Scientific Agricultural Society of Finland, 1957)
An attempt was made to elucidate the content of plant-available calcium, potassium and magnesium in different kinds of virgin peat. The amounts of these cations extracted by 1 N ammonium chloride solution were supposed to give an estimate satisfactory for this purpose. Also the extractable sodium was determined. The material consisted of 208 samples mainly collected from Northern Finland. The variation in the content of extractable cations was high in all the peat groups. The individual values of one group were overlapping the range of other ones. The average calcium and magnesium contents of the Sp, CSp and SCp groups were somewhat lower than those of Cp, BCp and EuSCp groups. The same seems to be the case, with the content of extractable sodium whereas the moss peats tended to be slightly less poor in potassium than the peats of better quality. A more or less significant correlation existed in all the peat groups between the calcium content and the pH-values. The correlation was markedly lower for pH and extractable magnesium. A weak tendency to negative correlation could be noticed between pH and extractable potassium. The land quality and the calcium and magnesium content of all the surface samples were correlated with each other, although not very strongly. Within the different peat groups no correlation between these quantities could be found, except in one case. The scant supply of potassium in the surface samples did not show any connection with the land quality. The reasons responsible to the large variation of the nutrient content within a certain peat group were discussed. The fact was emphasized that on the basis of the identification of the kind of peat nothing reliable is known of the nutrient content of the sample.